Effect of additional nutrients on Bio-methane production from anaerobic digestion of farming waste: Feasibility & Fertilizer recovery - Siddique, Md. Nurul Islam; Zaied, Khalid; Mohd Zamri, Ibrahim (Elsevier Ltd, 2020)
Various substrates digested together may be the supplement of lacks for the microbes engaged with anaerobic digestion. In the present work, the impact of nutrients on the co-digestion of farming substrates was evaluated. An additional supplement arrangement which assumes a key job in the anaerobic digestion was utilized at three distinct stages: 37 ◦C, 40 ◦C, and 50 ◦C. Outcomes demonstrated that at 37 ◦C by the use of supplements, biogas generation achieved 1.38-times than that of control. Besides, 40 ◦C without supplements represented an intriguing methodology because of the phenomenal utilization of this mid-temperature that had been found significant (56% of VS elimination and 8.4 L-biogas). The anaerobic co-digestion at 50 ◦C demonstrated that biogas generation likewise exceeded 11.3 L with supplements and that mL-CH4/g-VS were 1.24-times of that attained for the procedure without additional supplement. Outcomes for every temperature demonstrate that the supplement arrangement contributes to co-digestion. Moreover, 37 ◦C was the most used temperature on the modern scale and had the most effective influence on the use of supplements during the digestion process. Recovery of sludge was 0.09 m3 sludge / m3 substrate and the recovery of water was 0.86 (m3 sludge / m3 substrate) from the digester effluent. The digested sludge can be used as fertilizer and the by-product water can be used for irrigation purposes. The time required to regain the expenditures was observed as 3.77 y.